Medical and care compunetics 3 - Bos, Lodewijk (Studies in health technology and informatics, 2006)
For citizen/patient-related information, it is necessary to use the latest medical and care compunetics. This publication covers aspects concerning information supply to patient and professional; electronic health records, its standards, its social implications; and developments in medical and care compunetics.